2022
DOI: 10.3390/su142416545
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Multi-Level Inverter System for Grid-Tied DES Applications

Abstract: Energy harvesting from renewable energy sources is trending in the world due to inventions in modern technology. This paper proposes a grid-tied single-phase modified W-type 81-level inverter. Inverter design equations to calculate various parameters, such as the number of voltage levels and the number of DC power sources, along with the feedback controller equations, are developed to integrate the proposed topology with an electric power grid. The modeling of the control system for the proposed topology is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Single-power multilevel inverters mainly include capacitor types [9], diode types [10], hybrid clamp types [11], etc. The main advantages of the diode-type multilevel inverter are its simple structure, which can easily control the flow of power; however, it is difficult to equalize the pressure and difficult to expand [12]. The main advantage of a capacitive-type multilevel inverter is that it can expand multiple levels, and the large number of levels makes the overall efficiency of the inverter high [13].…”
Section: Introductionmentioning
confidence: 99%
“…Single-power multilevel inverters mainly include capacitor types [9], diode types [10], hybrid clamp types [11], etc. The main advantages of the diode-type multilevel inverter are its simple structure, which can easily control the flow of power; however, it is difficult to equalize the pressure and difficult to expand [12]. The main advantage of a capacitive-type multilevel inverter is that it can expand multiple levels, and the large number of levels makes the overall efficiency of the inverter high [13].…”
Section: Introductionmentioning
confidence: 99%
“…presents the comparative analysis of the proposed GTELI with existing Grid-Tied multilevel inverter topologies reported in the literatures[25][26][27][28][29][30][31][32][33][34][35], It is observed that the proposed GTELI has the highest level count,…”
mentioning
confidence: 99%